Enhanced recovery of rhamnolipid via foam fractionation from the fermentation broth of waste glycerol by Pseudomonas aeruginosa RS6 - Mahamad, Siti Syazwani; Mohamed, Mohd Shamzi; Radzuan, Mohd Nazren; Winterburn, James; Zakaria, Mohd Rafein (John Wiley and Sons, 2026)
Rhamnolipid (RL) biosurfactants are biodegradable and widely used in various industries due to their bioavailability. However, their recovery and purification from fermentation broth can be costly and often require the use of additional chemicals or solvents. In this study, RL produced from Pseudomonas aeruginosa RS6 using biodiesel side-stream waste glycerol as a substrate was recovered and enhanced using the foam fractionation method. Crucial factors in the gas–liquid adsorption process, including air flow rates, initial feed concentrations, and feed flow rates in batch and continuous stripping modes, were examined. In batch mode, a low air flow rate of 20 mL/min achieved a maximum RL enrichment of 1.49, indicating a 1.49-fold increase in RL concentration in the foamate compared to the feed, with a recovery rate of 81%. This finding confirms the importance of foam residence time in drainage activity, which is closely related to both enrichment and recovery. Additionally, a specified threshold level of enrichment was identified at 13 g/L of feed solution concentration, beyond which further increases were found to be impractical. In contrast, the continuous mode demonstrated a higher RL enrichment of 2.5 with a recovery rate of 51%, indicating its greater effectiveness for concentrating RL in less time. This study provides valuable insights into the gas–liquid interface's adsorption behavior under different operation modes, which is crucial for optimizing RL's recovery systems. The results contribute to the development of more efficient and sustainable biosurfactant recovery processes, particularly in simulating the early stage of industrial applications.